Perceptions of postnatal depression by healthcare practitioners in Malaysia - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2016)
Background: Postnatal depression (PND) is considered to be a serious mental health problem for many women worldwide; contributing to increased maternal morbidity and mortality. It is recommended that healthcare practitioners (HCPs) should have appropriate skills to assess psychological distress in women attending for antenatal and postnatal healthcare. However, little is known about the perceptions of Malaysian HCPs towards PND – and its assessment. The aims of this study were to: (i) explore the knowledge and perceptions of Malaysian HCPs about PND, (ii) explore how they currently manage PND and what helps and (iii) explore potential interventions for women with PND in Malaysia. Methods: A total of 18 HCPs involved with postnatal care in purposively selected clinics and a psychiatric ward in Kuala Lumpur, Malaysia were individually interviewed. Data were analysed using Framework Analysis. Results: The HCPs’ conceptualisations of PND do not reflect medical diagnostic criteria but are based on their professional experience and judgement of mainly the mother’s behaviour and childcare actions. The perceived causes for PND were explained by a psychosocial model reflecting the women’s own experiences (anxiety during pregnancy, psychological unreadiness for parenthood, childbirth experience, and roles and identity of being a mother), and contextual or cultural influences (traditional postnatal practices, cultural background and esoteric factors, lack of social support, and financial constraints) and the interplay between these two. There was a general lack of formal knowledge about PND among HCPs limiting detection of PND. Care practices were often limited to providing help with practical ‘mothering’ tasks. Conclusion: HCPs in maternal and child health require training in detection and management of PND. There is potential to prevent, educate and support women with PND through community-based interventions as agreed by the HCPs in this study.